Pelabelan Prima pada Kelas Graf Hasil Operasi Perkalian Tensor - Triwahyuniti, Suci; Rahmadani, Desi (Jambura Journal of Mathematics, 2026)
A graph  with a vertex set   is said to be a prime graph if there exists a bijective mapping , where  denotes the number of vertices in , such that for any two adjacent vertices  and  in  have . Tensor Product graph is a way to combine (compose) two graphs into one larger and more complex graph. The result is a new graph that reflects the connection properties of the two original graphs, but in a very specific and more complex way than other graph operations. Therefore, this research aims to determine whether there is prime labeling in the class of graphs resulting from the Tensor Product of the path graph  and the cycle graph . The research employed analytical and exploratory methods with a trial-and-error strategy to determine the labeling that possesses a prime property. The results of this study prove that two classes of the Tensor Product graph  for , and graph , for  are prime graph. This finding expands the results on classes of graphs that admit prime labeling  and provides a basis for further research on graph labeling in other graph operations